Pelatihan Kewirausahaan Berbasis E-Marketing Pada Kelompok Usaha Perempuan Anyaman Tikar Di Gampong Matang Gleum Kecamatan Peureulak Kabupaten Aceh Timur - Abdul Latief; Syardiansah Syardiansah; Muhammad Yakob (Universitas Medan Area, 2020)
The East Aceh Regency Community, Women's and Family Empowerment Agency (BPMPKS) through the field of women's empowerment currently has 21 productive business groups of poor women that have been running since 2010 until now. The productive business groups of these poor women have various types of business products that are run such as making cookies, presto milkfish, pandanus matting, grocery business, salted fish production, making organic fertilizers and others. One of the matting groups that has grown rapidly from the production side is the bungong chirih women's business group, which until now has more than 20 members. The results of the woven mat products provided are in great demand by the community because of the reliability quality can be proven. But from the marketing side it still needs further improvement to be able to develop. The current PKM activity is to provide e-marketing-based entrepreneurship training. This is because so far the marketing of the production of woven mats still revolves around the local scale. So with the entrepreneurship training, it is expected that the marketing scale can be broader and reach the five countries. Based on the results of this training, every member of the Chirih Bungon group has been able to use marketing media on line to market the matting products.